A case of perivascular epithelioid nodules arising in an intramural leiomyoma - Yoldez Houcine; Karima Mekni; Emna Brahem; Mouna Mlika; Aida Ayadi; Chiraz Fekih; Imene Ridene; Faouzi El Mezni (Elsevier, 2021)
Perivascular epithelioid cell (PEC) tumors (PEComas) are a family of related mesenchymal tumors composed of PECs that co-express melanocytic and smooth muscle markers. Their diagnosis is challenging in the female genital organs owing to its morphologic and immunohistochemical overlap with smooth muscle tumors and other clear cell tumors. We report the clinicopathologic and immunohistochemical characteristics. We also discuss differential diagnoses of an unusual tumor of the uterus composed of nodules of epithelioid cells strongly positive for HMB45, arising in a surrounding leiomyoma. We viewed these neoplasms as PEComa. The follow up has shown that the patient was alive without disease 1 year after the surgery.